The scarlet throne - Leow, Amy (Leow, Amy. False goddess trilogy, 2024)
"Binsa is a "living goddess," chosen by the gods to dispense both mercy and punishment from her place on the Scarlet Throne. But her reign hides a deadly secret. Rather than channeling the wisdom of an immortal deity, she harbors a demon. But now her priests are growing suspicious. When a new girl, Medha, is selected to take over her position, Binsa and her demon strike a deal: To magnify his power and help her wrest control from the priests, she will sacrifice human lives. She'll do anything not to end up back on the streets, forgotten and alone. But how much of her humanity is she willing to trade in her quest for power? Deals with demons are rarely so simple"--